Using Sequencing Technique for Diagnostic Different Species of Genus Rhizobium Which Isolated from Legume Plants - Al-Barhawee, Najwa Ibrahim Khaleel; Ahmed, Jasim M.Y. (Iraqi Journal of Science, 2022)
Samples of the root nodules were collected to isolate different species of the genus Rhizobium from several leguminous plants; Trigonella foenum-graecum, Medicago sativa, Lens culinaris, Vigna mungo, Vicia faba, Phaseolus vulgaris, and Cicer arietinum, and based on their morphological, cultural, and biochemical characteristics, in addition to the identification of each isolate at the species level by amplified polymerase chain reaction (PCR) and using the sequencing of the nitrogenous bases of the 16S rRNA gene, it was identified as Sinrhizobium meliloti, Sinrhizobium meliloti, Bradyrhizobium elkanii, Rhizobium leguminosarium biovar viciae, Rhizobium leguminosarium biovar phaseoli and Mesorhizobium cicero, respectively, (with the exception of bacteria isolated from Lens culinaris) it showed an agreement with the GenBank isolates with percentages ranging between (96-98) percent, as well as drawing the phylogenetic tree to determine the extent of evolution between these isolates and their convergence in the original with the international standard isolates.